Digital Transformation Through E-Master Application in Human Resource Development in Civil Servants - Fitriani, kharisma; Hidayat, Rofiq (IJCCS (Indonesian Journal of Computing and Cybernetics Systems), 2024)
The use of technology has become a crucial aspect in the progress and development of Human Resources (HR). HR management includes various aspects such as planning, organizing, compensation, and maintaining work relationships to achieve individual, organizational, and societal goals. Research in education has a significant impact on youth empowerment, a critical stage in human development. This study aims to describe motivation, personality, and skills in HR Development Management at the East Java Provincial Education Office Branch. Using a qualitative approach, this research understands HR development in depth through the "e-Master" application. The informants consisted of e-master application managers, personnel managers, and e-master application users. Data was collected through semi-structured interviews, primary documentation from direct observation, and non-participant observation. Data analysis was carried out using techniques of reduction, presentation, and drawing conclusions, with the validity of the data strengthened through triangulation of techniques and sources. It is hoped that the research results can improve the quality of human resources at the educational level, bringing a positive impact in empowering the workforce in education for a better future.